Dual exposure to smoking and household air pollution is associated with an increased risk of severe asthma in adults in Brazil. Issue 1 (10th December 2018) - Fernandes, Andréia Guedes Oliva; de Souza‐Machado, Carolina; Pinheiro, Gabriela Pimentel; de Oliva, Sergio Telles; Mota, Raquel Cristina Lins; de Lima, Valmar Bião; Cruz, Constança Sampaio; Chatkin, José Miguel; Cruz, Álvaro A.
Abstract: Background: The relationship between smoking, household pollution, dual exposure and severity of asthma in adults has not been sufficiently studied. We examined and compared the effects of cigarette smoking, domestic wood burning pollution and dual exposure (tobacco and wood burning) upon asthma severity in adults. Methods: This was a cross‐sectional study performed with 452 individuals with mild to moderate asthma and 544 patients with severe asthma (previously untreated). Smoking and exposure to wood smoke were identified and quantified through questionnaires to evaluate current and/or previous exposure; objective determination of cigarette exposure was obtained through the measurement of urinary cotinine. Asthma control was evaluated through Asthma Control Questionnaire; and severity was classified according to the Global Initiative for Asthma criteria. Subjects were grouped according to exposure type into 4 groups: smokers, household pollution, dual‐exposure and no‐exposure. Chi square, Mann–Whitney, and Kruskal–Wallis tests were used for comparisons between groups. Results: Out of 996 included individuals, 78 (7.8%) were exposed to cigarette smoking alone, 358 (35.9%) to household pollution alone, 155 (15.6%) to the two exposures combined and 405 (40.7%) were not exposed. Compared to unexposed individuals, exposure to household pollution resulted in poorer asthma control, higher proportion of severe asthma, and worse indicators of lung function. The double‐exposed individuals were worse off in all the evaluated parameters, and they were significantly worse than subjects with single exposure to household air pollution in relation to asthma severity and lung function. These subjects were predominantly females, older, with longer residence time in rural areas, lower income and lower schooling levels. Multivariate analysis showed that exposure to household pollution and double exposure were predictive factors associated with lack of control and increased severity of asthma. Conclusions: Exposure to household pollution is associated with poorer control, greater severity, and poorer pulmonary function; double‐exposed individuals have a greater risk of severe asthma and decreased lung function than those exposed only to household pollution.